Avaliação da ansiedade e da autoestima em mulheres no período gestacional - Nery, Nathália Gianini (2020)
Pregnancy is a time of intense changes for women, including physical, psychological, and hormonal changes in their bodies. Pregnancy is a period of risk, which may lead to emotional imbalance and directly influence anxiety and self-esteem. The study aimed to evaluate anxiety and self-esteem in women during the gestation period who undergo prenatal care in the urban Family Health Strategies Center of a city in the South of Minas Gerais. It is a descriptive-analytical, cross-sectional, and quantitative study carried out with 201 pregnant women. The study was approved by the Research Ethics Committee and data collection took place in late 2019 and early 2020 through interviews and the application of a socio-demographic questionnaire, data on pregnancy and significant events in life, the Hospital Anxiety and Depression Scale (anxiety sub-scale), and Rosenberg's Self-esteem Scale. Descriptive statistics, Cronbach's Alpha Coefficient, Pearson's Chi-squared, and Fisher's Exact tests, with a 5% significance level, were used for the data analysis. The odds ratio and the logistic regression were estimated. The results found that there was a higher frequency of pregnant women in the age group of up to 25 years old, who were married/cohabiting, Catholic, with a monthly family income ranging from 1001.00 to 2000.00 BRL, and who did not consume alcoholic beverages, tobacco or illicit drugs. Pregnant women reported unplanned pregnancy, usual risk as a type of prenatal care, the second trimester as the gestational age, no worries or problems with pregnancy, a good relationship with the newborn's father, and that they will receive support to take care of the baby. It was found that most pregnant women had not experienced anxiety and had average levels of self-esteem. The variables "change of mood" and "influence of physical change" during pregnancy in women's lives had a statistical association with anxiety. Pregnant women who reported experiencing mood swings were more likely to experience anxiety. Pregnant women who did not say that the physical changes influenced their lives were more likely to experience anxiety. No variable presented a statistical association with self-esteem. The variables anxiety and self-esteem presented statistical association, in which women in the gestation period with anxiety were more likely to have medium/low levels of self-esteem. It is required that healthcare practitioners, especially the nurses, notice possible signs of anxiety and changes in self-esteem during pregnancy in order to monitor and prevent future complications resulting from such changes, resulting in a healthy pregnancy for women and favoring the bond between mother and child. This research may bring advances in knowledge to this field, with the elaboration of protocols, continued education, and strategies that aim to provide completeness of assistance to women, resulting in improved self-esteem and the non-occurrence of anxiety throughout the entire gravidic-puerperal cycle.